Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 2644976 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "TaxonKey is Ceryle torquatus (Linnaeus, 1766)", "TaxonKey is Egretta alba (Linnaeus, 1758)", "TaxonKey is Hydranassa tricolor (Statius Muller, 1776)", "TaxonKey is Philohela minor (J.F.Gmelin, 1789)", "TaxonKey is Anthus spinoletta (Linnaeus, 1758)", "TaxonKey is Scardafella inca (R.Lesson, 1847)", "TaxonKey is Peucaea aestivalis (M.H.K.Lichtenstein, 1823)", "TaxonKey is Picoides arcticus (Swainson, 1832)", "TaxonKey is Peucaea carpalis Coues, 1873", "TaxonKey is Picoides borealis (Vieillot, 1809)", "TaxonKey is Spinus lawrencei (Cassin, 1850)", "TaxonKey is Colaptes chrysoides (Malherbe, 1852)", "TaxonKey is Setophaga americana (Linnaeus, 1758)", "TaxonKey is Porzana carolina (Linnaeus, 1758)", "TaxonKey is Setophaga graciae (S.F.Baird, 1865)", "TaxonKey is Baeolophus ridgwayi (Richmond, 1902)", "TaxonKey is Piranga flava (Vieillot, 1822)", "TaxonKey is Hydroprogne caspia (Pallas, 1770)", "TaxonKey is Acanthis hornemanni (Holböll, 1843)", "TaxonKey is Agelaius tricolor (Audubon, 1837)", "TaxonKey is Coccyzus erythropthalmus (A.Wilson, 1811)", "TaxonKey is Stelgidopteryx ruficollis (Vieillot, 1817)", "TaxonKey is Baeolophus wollweberi (Bonaparte, 1850)", "TaxonKey is Setophaga tigrina (J.F.Gmelin, 1789)", "TaxonKey is Sphyrapicus nuchalis", "TaxonKey is Chaetura vauxi (J.K.Townsend, 1839)", "TaxonKey is Empidonax hammondii (Xantus de Vesey, 1858)", "TaxonKey is Certhia familiaris", "TaxonKey is Ajaia ajaja (Linnaeus, 1758)", "TaxonKey is Corvus caurinus S.F.Baird, 1858", "TaxonKey is Aimophila ruficeps (Cassin, 1852)", "TaxonKey is Phalacrocorax penicillatus (Brandt, 1837)", "TaxonKey is Contopus cooperi (Nuttall, 1831)", "TaxonKey is Charadrius nivosus (Cassin, 1858)", "TaxonKey is Sialia currucoides (Bechstein, 1798)", "TaxonKey is Setophaga fusca (Statius Müller, 1776)", "TaxonKey is Anas fulvigula Ridgway, 1874", "TaxonKey is Piranga rubra (Linnaeus, 1758)", "TaxonKey is Empidonax minimus (W.M.Baird & S.F.Baird, 1843)", "TaxonKey is Vireo plumbeus", "TaxonKey is Anas strepera Linnaeus, 1758", "TaxonKey is Anas rubripes", "TaxonKey is Charadrius alexandrinus Linnaeus, 1758", "TaxonKey is Setophaga occidentalis (J.K.Townsend, 1837)", "TaxonKey is Loxia leucoptera J.F.Gmelin, 1789", "TaxonKey is Anas cyanoptera Vieillot, 1816", "TaxonKey is Vireo huttoni", "TaxonKey is Setophaga dominica (Linnaeus, 1766)", "TaxonKey is Setophaga townsendi (J.K.Townsend, 1837)", "TaxonKey is Quiscalus mexicanus", "TaxonKey is Contopus sordidulus P.L.Sclater, 1859", "TaxonKey is Pica pica (Linnaeus, 1758)", "TaxonKey is Charadrius semipalmatus Bonaparte, 1825", "TaxonKey is Setophaga virens (J.F.Gmelin, 1789)", "TaxonKey is Sitta pygmaea Vigors, 1839", "TaxonKey is Piranga ludoviciana (A.Wilson, 1811)", "TaxonKey is Quiscalus major Vieillot, 1819", "TaxonKey is Melanerpes formicivorus (Swainson, 1827)", "TaxonKey is Strix varia Barton, 1799", "TaxonKey is Actitis macularius (Linnaeus, 1766)", "TaxonKey is Setophaga palmarum (J.F.Gmelin, 1789)", "TaxonKey is Melanerpes erythrocephalus (Linnaeus, 1758)", "TaxonKey is Vireo gilvus (Vieillot, 1808)", "TaxonKey is Vireo bellii Audubon, 1844", "TaxonKey is Anas americana J.F.Gmelin, 1789", "TaxonKey is Acridotheres tristis (Linnaeus, 1766)", "TaxonKey is Acanthis flammea (Linnaeus, 1758)", "TaxonKey is Spinus psaltria (Say, 1822)", "TaxonKey is Sitta pusilla Latham, 1790", "TaxonKey is Peucaea cassinii (Woodhouse, 1852)", "TaxonKey is Aphelocoma ultramarina (Bonaparte, 1825)", "TaxonKey is Gallinago gallinago (Linnaeus, 1758)", "TaxonKey is Anas carolinensis J.F.Gmelin, 1789", "TaxonKey is Bartramia longicauda (Bechstein, 1812)", "TaxonKey is Geothlypis formosa (A.Wilson, 1811)" ] }, { "or" : [ "BasisOfRecord is Human Observation", "BasisOfRecord is Observation", "BasisOfRecord is Machine Observation" ] }, "Country is United States of America", "HasCoordinate is true", "HasGeospatialIssue is false", "Year is greater than or equal to 1949", "Year is less than or equal to 2011", "Month is greater than or equal to March", "Month is less than or equal to August" ] } The dataset includes 2644976 records from 13 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0051821-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences